Excitation functions for Sc radioisotopes production via (α,x) nuclear reactions on natural calcium up to 25 MeV; Radiation Physics and Chemistry; Vol. 227 - Khasnovo L. A. Lutfi Aditjya; Garapatski A. A. Alexander Alexandrovich; Villa Pineda N. E. Nelson Enrrique; Larkina M. S. Mariya Sergeevna; Lomov I. V. Ivan Viktorovich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2025, 2025)
Title screen